PENERAPAN PERMAINAN DADU HURUF UNTUK MENINGKATKAN BAHASA ANAK KELOMPOK B RA AL-FATTAH KARANGDUREN PAKISAJI MALANG - Afdilatul Ilmiah; Devi Wahyu Ertanti; Ika Anggraheni (Jurnal Dewantara, 2020)
The kid's world is playing, activities are the children's natural activities, playing is also instrumental in early childhood development because by playing children feel excited, Learn new things, build creativity to the fullest, and can stimulate various aspects of development. Researchers find learning facts That some language proficiency is especially in understanding the early literacy is quite low, Because it often uses LKA cause passive children, teachers can not attract attention Child's interest in learning, and the element of playing in learning  the least so the kid bored quickly, Based on it Researchers use Dice Game aims to improve various aspects of development. But researchers focus only on one aspect of development language aspect. With Game dice letters children are able to recognize the sound of alphabet which has been arranged according to the picture card. Using the game Then student language skills Group B RA Al-Fattah experience increased Where at the beginning of the pre observation cycle reaches 0%, However, after implemented class action research practice using the first character dice game experienced an increase 26,3%, and experienced improvements in the study of the 89,5% that have reached the indicator prescribed by researchers.